Pengembangan Media Pembelajaran Menggunakan Aplikasi Book Creator pada Materi Bangun Ruang di Kelas V Sekolah Dasar - Rani Pausa; Melva Zainil (Universitas Negeri Padang, 2023)
This research is motivated by the lack of use of learning media that keeps up with the times in elementary schools. The aim of this research is to produce learning media that are valid and practical using the Book Creator application on geometric materials in class V of Elementary School. This type of research is development research (R&D) using the ADDIE model with the stages of analysis, design, development, implementation, and evaluation. Learning media were tested for validity by a team of experts and practice tests with the responses of educators and students. Validity data was sourced from material experts 85.57%, linguists 95%, and media experts 97.5%. The average validation score is 92.69% with a very valid category. The practicality test was obtained through questionnaires given to educators by 97,5% and students by 97.03%. The average practicality test result is 97.26% in the very practical category. Thus, the results of the study indicate that the learning media that have been developed using the Book Creator application are very valid and practical to use in elementary schools and this research recommends educators to use learning media that are interesting and meaningful for students.